Aging and immunotherapies: New horizons for the golden ages. Issue 1 (30th September 2020) - Hamilton, Jamie A.G.; Henry, Curtis J.
Abstract: The life expectancy of the world's elderly population (65 and older) continues to reach new milestones with older individuals currently comprising greater than 8.5% (617 million) of the world's population. This percentage is predicted to approach 20% of the world's population by 2050 (representing 1.6 billion people). Despite this amazing feat, many healthcare systems are not equipped to handle the multitude of diseases that commonly manifest with age, including most types of cancers. As the world's aging population grows, cancer treatments continue to evolve. Immunotherapies are a new drug class that has revolutionized our ability to treat previously intractable cancers; however, their efficacy in patients with compromised immune systems remains unclear. In this review, we will discuss how aging‐associated losses in immune homeostasis impact the efficacy and safety of immunotherapy treatment in preclinical models of aging. We will also discuss how these findings translate to elderly patients receiving immunotherapy treatment for refractory and relapsed cancers, as well as, strategies that could be explored to improve the efficacy of immunotherapies in aged patients. Abstract : Aging is associated with increased cancer incidence and immunological decline. Given the increased use of immunotherapies for treating cancer, this review focuses on summarizing results from studies conducted in aged mouse models and clinical trials reporting data specifically on aged study participants.